2021
DOI: 10.1111/papt.12372
|View full text |Cite
|
Sign up to set email alerts
|

‘Like jumping off a ledge into the water’: A qualitative study of trauma‐focussed imaginal exposure for hearing voices

Abstract: Objective There is growing evidence of a link between the experience of hearing voices and past traumatic events, and trauma‐focussed psychological interventions are being applied to hearing voices as an emerging treatment direction. To inform the ongoing development and implementation of this application, there is a need to understand clients’ therapy experiences. Design Qualitative study exploring the experience of people who received an intervention for voices linked to a previous traumatic event. Method Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…some did not have a secure place to live), or that they might have needed more preparatory work before moving to the trauma-processing stage. Consistent with our results, a qualitative study exploring the experiences of trauma-focused imaginal exposure for voice hearing found that people's therapy experience can be negatively affected by outside circumstances, 52 and highlighted the need for a supportive environment outside of therapy. Others have also highlighted the importance of offering trauma-focused interventions in a multidisciplinary setting.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…some did not have a secure place to live), or that they might have needed more preparatory work before moving to the trauma-processing stage. Consistent with our results, a qualitative study exploring the experiences of trauma-focused imaginal exposure for voice hearing found that people's therapy experience can be negatively affected by outside circumstances, 52 and highlighted the need for a supportive environment outside of therapy. Others have also highlighted the importance of offering trauma-focused interventions in a multidisciplinary setting.…”
Section: Discussionsupporting
confidence: 87%
“… 48 One reason for this is that clinicians fear that addressing trauma may lead to an increase in the severity of positive symptoms or suicidal behaviour. 49 Our findings expand the research available so far on the application of trauma-focused therapies in people with psychotic symptoms 50 , 52 and show that EMDR can be acceptable and helpful for people with ARMS.…”
Section: Discussionsupporting
confidence: 72%
“…The risk of ongoing victimization was also highlighted by two cases, with psychosocial stressors in the form of actual or threatened reoccurrence of their index traumas leading to a clinically significant deterioration in PTSD, undermining previous gains and thus emphasizing the need for ongoing safety management. Similarly, Brand et al ( 69 ) conducted a qualitative analysis of a case series of PE for voice hearing ( 16 ) and recommended monitoring and adaptions to therapy where indicated, after finding the therapy experience was negatively impacted by aversive external circumstances. Social work and safeguarding interventions may be necessary in these cases, further highlighting the value of delivering tf-CBTp in a multidisciplinary setting.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with those from a randomised controlled trial ( n = 40) of ImRs for post‐traumatic nightmares that found significant reductions in perceived incompetence, which compared to other trauma‐related beliefs, was most strongly associated with PTSD symptom reduction (Long et al, 2011). Furthermore, preliminary evidence suggests that negative affect, emotion regulation deficits and dissociative coping mediate the pathway from trauma to hallucinatory experiences (Strachan, Paulik, Preece et al, 2023), and past qualitative findings suggest trauma‐focussed treatments enhance skills to constructively cope with distress (Feary et al, 2022) and stand up for oneself (Bosch & Arntz, 2021). Bandura (1997) suggests that encouragement from credible others, experiences of successful performance and physiological feedback influence self‐efficacy.…”
Section: Discussionmentioning
confidence: 99%